6x-(x+3)=2

Simple and best practice solution for 6x-(x+3)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(x+3)=2 equation:


Simplifying
6x + -1(x + 3) = 2

Reorder the terms:
6x + -1(3 + x) = 2
6x + (3 * -1 + x * -1) = 2
6x + (-3 + -1x) = 2

Reorder the terms:
-3 + 6x + -1x = 2

Combine like terms: 6x + -1x = 5x
-3 + 5x = 2

Solving
-3 + 5x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 5x = 2 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = 2 + 3
5x = 2 + 3

Combine like terms: 2 + 3 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| 9n+3n^2=176.75 | | x^4-7x^2+16=0 | | 3p+6=6-p | | 16(v+1)-4v=4(3v+1)-7 | | M+2m+-6=-12+2m | | y^2dx+(3xy+y^2-1)dy=0 | | A=5n-600 | | y=.5x-10 | | 4z+z+5=z | | -19=x+3(2x-4) | | -3x+15=2x-2 | | 31=s+2.5s+10 | | 10x^2-5=0 | | 2(12-4y)+4y=24 | | 7g-21=16 | | sqrt(x+21)-1=x | | 5f-3=32 | | 183=-w+87 | | X-26=12 | | 25m^2a^2-4a^2= | | 3(12)+y=36 | | 4.7m=18-2.7m | | 12k+50=40 | | 49x-16x^3=0 | | -2=(7y-8y)2+14 | | (9n+4)+(3n^2-0.75)=180 | | -5h-13=-28 | | x^2-70=7x | | -x+5=2(x-8) | | 10x-6=3x-5 | | W-26=12 | | 9x+6y=n |

Equations solver categories